Epidemiology of Buruli ulcer and of Mycobacterium ulcerans transmission in Cameroon. - (:unkn) unknown (My University, 2014)
Buruli ulcer (BU) is a tropical disease caused by Mycobacterium ulcerans. It appears as cutaneous lesions causing severe morbidity and permanent incapacities in affected populations. BU occurs mainly in West and Central Africa, where it is found endemic in very localized regions. The transmission mode of M. ulcerans to humans remains mysterious, which, combined with the lack of basic epidemiological knowledge on the disease, hampers considerably the design of effective control strategies. The goals of this thesis were to identify the different risks associated with Buruli ulcer, and to contribute to the improvement of knowledge on the circulation and transmission of M. ulcerans. We studied two Buruli ulcer foci in Cameroon, and analyzed the individual, behavioral, spatial and temporal risk factors for BU. We described populations groups, environments and seasons at higher risk. We also engaged in entomological fieldwork to verify if M. ulcerans was circulating in the domestic environment, an hypothesis never tested in African endemic regions. We identified several taxa carrying M. ulcerans, and possible vector candidates among them.This work proposes an update of the knowledge on Buruli ulcer epidemiology in Cameroon, and several results can be transposed to other endemic regions, especially in Central or West Africa, where endemic areas present similar environments. These results could provide useful elements to design more efficient public health strategies against Buruli ulcer and to target them accurately to populations, places and persons at highest risk. These results finally suggest new leads for future research on the mode of transmission of M. ulcerans.
Keywords: African Research